Spontaneous resolution of dermatomyositis associated with fallopian-tube carcinoma following staging surgery: A case report. Issue 10 (March 2019) - Lin, Chen; Ying, Zheng; Sijing, Chen
Abstract: Rationale: Paraneoplastic dermatomyositis (DM) is an inflammatory disease of the connective tissue caused by immunologic events in the presence of malignant tumors, which are typically related to ovarian, pancreatic, stomach, and colon cancer. Traditional treatment of paraneoplastic DM includes combination therapy for the underlying malignancy with systemic steroids. Patient concerns: A 41-year-old woman presented with facial erythema and myalgia of the extremities. Diagnosis: The patient was diagnosed with DM associated with a fallopian-tube carcinoma. Interventions: The cancer staging surgery was performed via muilt-port laparoscope and administered 6 cycles of adjuvant chemotherapy with paclitaxel (210 mg) and carboplatin (600 mg) right ovary and the left fallopian tube were removed laparoscopically. Outcomes: The DM healed spontaneously without the use of general glucocorticoids after the cancer staging surgery. During the 9-month follow-up, no recurrence of DM or neoplasm was observed. Lessons: This case highlights the fact that paraneoplastic DM can heal spontaneously after therapy for the underlying neoplasm, thereby avoiding the use of systemic steroids and their side effects. Moreover, DM can be an initial symptom for gynecological cancer such as fallopian-tube cancer. Thus, if DM is refractory to standard treatment, gynecological neoplasms should be considered.